Two-Dimensional MoS2-Based Photosensitive Al/MoS2/SiO2/Si/Ag MOS Capacitor - Das S.; Kumar C.; Kumar R.; Srivastava A.; Jit S. (My University, 2025)
This paper reports the seamless fabrication of an Al/MoS2/SiO2/Si/Ag structure metal-oxide-semiconductor (MOS) photosensitive capacitor using two-dimensional (2D) MoS2 films. The 2 nm MoO3 thin film is transformed into a 2D MoS2 film through sulfurization in the vapor phase reaction. The morphological, structural and photophysical properties of the transformed MoS2 films are investigated using Raman spectroscopy, atomic force microscopy, energy-dispersive X-ray spectroscopy, UV-Vis spectroscopy, and X-ray photoelectron spectroscopy. It is found that the grown MoS2 films are of good quality and continuous over the entire surface. The fabricated MoS2 based MOS capacitor is electrically characterized through aluminum and silver contacts. When the MOS capacitor is exposed to light, its capacitance is observed to be increasing with the light intensity. The unbiased capacitance of 477 pF under dark condition is increased to 591 pF when exposed with light ( $\lambda \sim ~600$ nm) of 500 $\mu \text{W}$ /cm2 © 1989-2012 IEEE.